Features of Phenotypic Manifestations, Anamnesis, Connective Tissue Metabolism among Children on the Background of Acute Bronchitis - Strelkova, M.; Senatorova, G. (My University, 2020)
High population frequency with the prevalence of connective tissue dysplasia, the unique role of connective tissue in the exercise of various functions of organs and systems of the body significantly affects the clinical course of bronchopulmonary diseases in children. The relationship between the presence of tracheobronchial dyskinesia and other phenotypic signs of "weakness" of connective tissue is noted. The clinical significance of tracheobronchial dyskinesia is that it is one of the causes of bronchial obstruction and chronic cough. Through mechanisms of hyperventilation and local inflammation, bronchial obstruction can lead to the development of emphysema, chronic bronchitis, and pulmonary heart. The study included 72 inpatients (the 1st group comprised 41 children with acute obstructive bronchitis and the 2nd group had 31 children with acute bronchitis simple). To assess the status of connective tissue metabolism, the daily excretion of the metabolite of connective tissue – oxyproline in the daily urine sample was determined. The metabolism of glycosaminoglycans was studied by the level of uronic acids in the urine. The level of blood glycosaminoglycans was determined. In establishing the presence of connective tissue dysplasia, the levels of stigmatization (a conditional index that includes the total number of connective tissue dysplasia points with the allocation of low, medium and high levels) were taken into account using the table "Indicators in the severity of connective tissue dysplasia". During the analysis of connective tissue metabolism in the serum of children with acute bronchitis complicated by broncho-obstructive syndrome with connective tissue dysplasia we observed phenotypic changes in the form of a decrease in the total level of the glycosaminoglycans, 2 and 3 fractions of the glycosaminoglycans, as well as an increase in the concentration of chondroitin sulfates of urine. Phenotypic portrait of children of the first group was characterized by dysplastic disorders of the skeleton, skin and its appendages, eyes, ears. From the list of external manifestations of dysmorphogenesis of children of this group, including 55 dysplastic signs, 24 (43.6%) were absent in children of the second group. The unfavorable factors of the formation of a syndrome of bronchial obstruction include the age of a mother older than 30 years and father's age older than 36 years, children born of the 3rd or more pregnancies and childbirth, and burdened with an antenatal period of development of the fetus (anemia in pregnant women, manifestations of pregnancy gestosis, threat of premature abortion) and bad habits (including smoking) of mothers during this pregnancy. Connective tissue dysplasia causes prolongation of cough symptoms and physical changes (in the form of box shades of percussion sound, hard breathing, dry and damp mid-rash wheezing), which lead to the need of longer usage of mucolytic drugs.
Keywords: acute bronchitis; connective tissue dysplasia